Toán ứng dụng trong đời sống - IA. I. Perelman; GS. Nguyễn Đình Dậu; TS. Nguyễn văn Tâm; TS. Nguyễn Văn Út (Đồng Nai NXB Đồng Nai, 1986)
Ứng dụng toán học trong dời sống
Keywords: IA. I. Perelman; Toán; Ứng dụng; Đời sống